Be-langea Healing Ritual: Living Qur'an among the Rejang Community of Bengkulu, Indonesia - Fitra, Akhmad Aidil; Sari, Yuni Purnama; Reza Liana; Jafar; Japarudin; Idi Warsah (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2026)
Studies on the living Qur'an have predominantly focused on recitation practices, amulets, and ruqyah within mainstream Muslim communities, while largely overlooking the ways in which Qur'anic verses are integrated into indigenous healing systems through material objects, spatial rituals, and local cosmologies among peripheral ethnic communities. This article addresses that gap by examining be-langea, a traditional healing ritual practiced by the Rejang community in Dusun Sawah, Bengkulu, Indonesia, in which water and lime (jeruk nipis) function as the principal therapeutic media through which Qur'anic verses are materially activated and spatially mediated. Employing a qualitative research design that combines ethnographic fieldwork with phenomenological analysis, the study draws on data collected through in-depth interviews with five key informants: two traditional healers, two patients, and one community leader, as well as participatory observation conducted over a period of more than one month. Guided by Rafiq's informative–performative framework, the findings make three principal theoretical contributions. First, be-langea demonstrates a process of Qur'anic materialization in which the sacred text is transferred into physical substances and enacted through bodily gestures and domestic spaces, thereby extending its performative function beyond verbal recitation. Second, the informative and performative dimensions operate as mutually constitutive rather than sequential mechanisms. Third, the dukun functions as a cultural broker who actively negotiates Islamic legitimacy for indigenous healing practices amid ongoing reformist pressures. By foregrounding the material and spatial dimensions of Qur'anic engagement, this study advances living Qur'an scholarship through a framework that illuminates how Muslim communities enact and embody sacred texts across the full spectrum of their cultural resources.